PELESTARIAN BUDAYA MELALUI SANGGAR BUDAYA KAMENGMI DI DESA KAMOT KECAMATAN ALOR TIMUR LAUT - Senti Atakari; Salomi Duka, Saron Lalangpuling, Safri Malaka, Saptarika Mikidori, Riflyisrianly Beri Ledang, Halena (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
This research aims to present Cultural Preservation through Kamengmi Cultural Studio in Kamot Village, Alor Timur Laut District. The research method used descriptive qualitative analysis. data collection techniques were carried out in two ways, observation and interviews. this research was conducted in kamot village hamlet 1 RW 02 RT 04 Alor Timur Laut sub-district, Alor district. information in this study is the founder of the Kamengmi studio, namely Mr Maklon Kamenglang. The results of this study show that: (1) The Origins of Kamengmi Cultural Studio in Kamot Village; (2) The Establishment of Kamengmi Cultural Studio as an Effort to Preserve Local Culture; (3) Programmes and Activities in Kamengmi Cultural Studio; (4) The Role of Kamengmi Cultural Studio in Strengthening Local Cultural Identity; (5) Social and Economic Impact on Kamot Village Community; (6) Challenges Faced by Kamengmi Cultural Studio. The results of this study can be concluded that Kamengmi Culture in Kamot Village has a very large role in the preservation of local culture. Through teaching dances, songs, and cultural values, this studio not only preserves cultural heritage but also strengthens the identity of the local community.